Phase II, open-label, randomized, multicenter trial (HERBY) of Bevacizumab in pediatric patients with newly diagnosed high-grade glioma - Grill, Jacques; Massimino, Maura; Bouffet, Eric; Azizi, Amedeo A.; McCowage, Geoffrey; Cañete, Adela; Saran, Frank; Le Deley, Marie-Cécile; Varlet, Pascale; Morgan, Paul S.; Jaspan, Tim; Jones, Chris; et al. (American Society of Clinical Oncology, 2018)
Purpose Bevacizumab (BEV) is approved in more than 60 countries for use in adults with recurrent glioblastoma. We evaluated the addition of BEV to radiotherapy plus temozolomide (RT+TMZ) in pediatric patients with newly diagnosed high-grade glioma (HGG). Methods The randomized, parallel group, multicenter, open-label HERBY trial (ClinicalTrials.gov identifier: NCT01390948) enrolled patients age ≥ 3 years to ≤ 18 years with localized, centrally neuropathology-confirmed, nonbrainstem HGG. Eligible patients were randomly assigned to receive RT + TMZ (RT: 1.8 Gy, 5 days per week, and TMZ: 75 mg/m² per day for 6 weeks; 4-week treatment break; then up to 12 3 28-day cycles of TMZ [cycle 1: 150 mg/m² per day, days 1 to 5; cycles 2 to 12: 200 mg/m² per day, days 1 to 5]) with or without BEV (10 mg/kg every 2 weeks). The primary end point was event-free survival (EFS) as assessed by a central radiology review committee that was blinded to treatment. We report findings of EFS at 12 months after the enrollment of the last patient. Results One hundred twenty-one patients were enrolled (RT+TMZ [n = 59]; BEV plus RT+TMZ [n = 62]). Central radiology review committee–assessed median EFS did not differ significantly between treatment groups (RT+TMZ, 11.8 months; 95% CI, 7.9 to 16.4 months; BEV plus RT+TMZ, 8.2 months; 95% CI, 7.8 to 12.7 months; hazard ratio, 1.44; P = .13 [stratified log-rank test]). In the overall survival analysis, the addition of BEV did not reduce the risk of death (hazard ratio, 1.23; 95% CI, 0.72 to 2.09). More patients in the BEV plus RT+TMZ group versus the RT+TMZ group experienced one or more serious adverse events (n = 35 [58%] v n = 27 [48%]), and more patients who received BEV discontinued study treatment as a result of adverse events (n = 13 [22%] v n = 3 [5%]). Conclusion Adding BEV to RT+TMZ did not improve EFS in pediatric patients with newly diagnosed HGG. Our findings were not comparable to those of previous adult trials, which highlights the importance of performing pediatric-specific studies.